Predictors of Intention to Interact with Apparel Products on Instagram: Do creativity and Positive Emotions Matter? - Wardana, Candra Kusuma; Prasetya, Farid Adi; Maimun, Muhammad Halim; Fatchan, Fuad Hudaya (Jurnal Manajemen Bisnis, 2024)
Research aims:  This research aims to determine the effect of perceived creativity, positive emotion, affective commitment on people intention to interact.Design/Methodology/Approach: The population in this research was Instagram users who experienced online purchasing fashion product from July to December in 2023. The sampling technique is employed purposive sampling to decide 225 respondents. The data has been examined for validity and reliability. The data analysis method used quantitative and descriptive.  A Structural Equation Modelling (SEM) approach is used for data analysis using Smart PLS.Research findings: Our study found a positive relationship between perceived creativity and positive emotion, as well as affective commitment. On the other hand, the study also revealed that perceived creativity does not have a positive correlation with users’ interaction intention. Similarly, positive emotion did not show a positive relationship with affective commitment. However, the study also demonstrated a positive correlation between positive emotions and affective commitment with people’s intention to interact.Theoretical Contribution/Originality:  this study gives meaningful contribution to Stimulus-Organism-Response theory by incorporating creativity to assess Instagram social media platform.Practitioners/Policy Implications:  These findings can assist business owners and social media marketers in developing creative marketing campaigns and building strong bond with their followers.Research Limitations/Implications: the limitation of this study is only assessing Instagram on fashion industry. Future research could replicate the study with different industries and collect respondent with a specific occupation to get better understanding on online consumer behavior